Angular selective light transmission characteristics of a grating optical filter ** - Rustam Sabirovich Zakirullin (Advanced Engineering Research, 2015)
The grating optical filters are investigated to determine the degree of impact of the geometric grating parameters on the angular characteristics of the light transmission. The filter consists of a plane-parallel transparent substrate with thin-layer gratings on two surfaces. The gratings are formed by alternating transmitting and absorption bands. The relative position of two gratings provides angular selectivity of the light transmission. A graphic-analytical method is developed to determine the angular characteristic of the filter light transmission in the form of the dependence of the light transmission coefficient on the beams incidence angle. The effect of a filter characteristic angle (this angle determines a shift of the gratings on the input and output surfaces), fringe spacing (fringe spacing on each grating is equal to the total width of two adjacent alternating bands), and fringe ratio (relation of the fringe spacing of the input and output gratings) on the angular characteristics of the light transmission. The filter characteristics in the areas of decreasing and increasing transmittance are equidistant, linear, and symmetrical with respect to the characteristic angles of the filters in the range of the incidence angles from 0° up to 60°. At large incidence angles, equidistance, linearity, and symmetry of the characteristics are violated. The obtained regularities should be considered when determining the geometrical parameters of the filters satisfying the required for the specified glazed construction and the preset angular characteristics of the light transmission. It is advisable to apply the filter in the areas where the light transmission control is needed at the change of the beams incidence angle due to the movement of a light source and/or a glazed object relative to each other, especially in architectural glazing.